Gang Related - Kouf, Jim.; Belushi, James, 1954-; LelaRochon; TupacShakur (USA Kouf/Bigelow Productions, 1997)
Two cops kill an undercover DEA agent by mistake, and frantically try to cover their tracks by framing a homeless man for the crime. That involves juggling evidence, coaching witnesses, and improvising to keep their desperate scheme from unraveling.
Two cops kill an undercover DEA agent by mistake, and frantically try to cover their tracks by framing a homeless man for the crime...
Jim Kouf
Languages : English, French, Spanish
Subtitles : English, French, Spanish
Keywords: Drama; Crime